TEACHER COMPETENCY DEVELOPMENT STRATEGIES TO IMPROVE EDUCATION QUALITY - Akbar, Muhammad Aqil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Education is the main foundation for sustainable community development and increasing the nation's competitiveness in the era of globalization. The role of teachers as the spearhead in the teaching-learning process is vital in determining the future of the younger generation. However, not all teachers have adequate competencies to face new challenges in education. This study aims to identify effective teacher competency development strategies for improving the quality of education. The research uses a qualitative descriptive method with a literature study approach to analyze various strategies that have been documented in the literature. The results of the analysis show that the development of pedagogical, technological, managerial, and social competencies is essential to improve the quality of learning. Institutional support, and collaboration among teachers, as well as the involvement of parents and the government, are key to the success of teacher competency development. The implications of this research are significant in formulating more effective education policies and teaching practices, with the ultimate goal of improving the quality of education globally.